Corrosión del refuerzo de acero del concreto. Caso histórico "Puente sobre el Lago de Maracaibo en Venezuela" - de Rincón, Oladis (Revista Técnica da Faculdade de Engenharia da de Zulia)
A brief review is given on the corrosion of reinforcing steel in concrete structure exposed to salt water action. The influence of the chemical and physical factors on the corrosion of the reinforcing steel detected in the Lake of Maracaibo Bridge- “General Rafael Urdaneta” is use to illustrate the causes and the mechanic under which this bridge is deteriorating. The methods for preventing corrosion in this structure were also studied on laboratory and field scales. The results indicate the corrosion in this bridge is due to the penetration of the chloride ions from environment because of the low thickness of concrete covering of the steel structure, it is shown that the cathodic protection with Aluminum-Zinc-Indio anodes can be used in some part of the bridge.